2013
DOI: 10.3126/ijim.v2i2.8319
|View full text |Cite
|
Sign up to set email alerts
|

Direct Nitrate Reductase Assay for detection of drug resistance in Mycobacterium tuberculosis: rapid, simple and inexpensive method for low resource laboratories

Abstract: INTRODUCTION: The most common method for detection of drug-resistant-Tuberculosis (DR-TB) in resource-limited settings (RLSs) is indirect susceptibility testing on Lowenstein-Jensen (LJ) medium with results available only after 2-3 months. Rapid detection of drug resistance by direct Nitatre Reductase Assay (NRA) expedites Tuberculosis patient management. The objective of the study is to access the feasibility and performance of Direct NRA for detection of DR-TB in National Tuberculosis Center under the Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…The results by NRA were obtained much earlier (19.3 days) than the conventional PM (72 days) where majority (82.7%) of the positive results was available within 21 days. In contrast to our results, Satti et al and Lamsal et al have reported high sensitivity of 100% for RIF and more than 97% for INH [ 9 , 16 ]. However, our findings were consistent with the results of majority of the studies where NRA was done directly on sputum samples [ 17 – 19 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The results by NRA were obtained much earlier (19.3 days) than the conventional PM (72 days) where majority (82.7%) of the positive results was available within 21 days. In contrast to our results, Satti et al and Lamsal et al have reported high sensitivity of 100% for RIF and more than 97% for INH [ 9 , 16 ]. However, our findings were consistent with the results of majority of the studies where NRA was done directly on sputum samples [ 17 – 19 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This paper reports on research that explores the knowledge, attitudes and practices of community members in relation to antibiotic use in the Rupandehi district in Nepal. Previous studies in Nepal have investigated surgical site infection and antibiotic use [29], antibiotic resistance [30–33], antibiotic prescribing and sensitivity [34], antibiotic prescribing patterns [35, 36], antibiotic dispensing practices [37], knowledge, attitudes and practices of medical students in relation to antibiotics use [38], and dispensing practices and patients’ knowledge about drug use [39]. However, to our knowledge no population based studies have been conducted on knowledge, attitudes and practices relating to antibiotics use.…”
Section: Introductionmentioning
confidence: 99%
“…14 Hence it is important to know the resistant to RIF. Our study is in complete concordance with the studies using direct nitrate reductase assay for drug susceptibility testing of M. tuberculosis conducted by.Affolabi et al, 12 Mishra et al, 15 Thapa et al 16 In resource-constraint areas cost is an imperative aspect where most of the disease is prevalent. A cost by NRA as compared with PM and molecular assays accentuates the need of this colorimetric assay to be routinely used in laboratories in low-income countries.…”
Section: Discussionmentioning
confidence: 99%